Pengembangan Media Komik Berbasis Model Problem Based Learning pada Materi Daur Hidup Hewan Kelas IV SD - Elinda Safitri; Imelda Ratih Ayu; Patricia H.M Lubis (STKIP Andi Matappa Pangkep, 2022)
This type of research is Research and Development (R&D). This study uses the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The purpose of this research is to develop a comic media based on the Problem Based Learning model on animal life cycle material for grade IV SD which is valid, practical, and effective. Data collection techniques used are questionnaires and tests. The results of data analysis showed that the comic media developed in a very valid category based on a validation questionnaire sheet by 3 experts, namely media experts, linguists, and material experts with an average validity value of 90,2%; comic media developed in the very practical category based on trials to students with an average practicality value of 91,9% (one to one) and 88,7% (small group); comic media which was developed in the very effective category based on the final test of student learning outcomes with an average effectiveness score of 86%. Thus, it can be concluded that the comic media based on the Problem Based Learning model on animal life cycle material that has been developed is very valid, practical, and effective.